Gettoizacja Budapesztu 1944–1945. Zarys problemu - Piotrkowiak-Junkiert, Kinga (Zagłada Żydów. Studia i Materiały, 2016)
An article refers to the ghettoization of Budapest, which plans was created just after when German troops invaded Hungary on 19 March 1944. Paper presents particular stages of the Jews’ fate in Budapest. Which were: duty of wearing the yellow-stars, establishment of the ‘Yellow-star Houses’ and ‘Protected Houses’, moreover a movement to ghetto, which was established on 5 December 1944. An article contains an analyse of ghettoization theme with an example of the ‘large ghetto’, ‘international ghetto’ and also refers to the people’s fates which rescued Jews (‘Righteous among the Nations’).